Administrative Headquarters of the Forestry Foundation: A study of the design process, construction technique, structure and environment - Meirelles, Célia Regina Moretti; Camargo, Helena Dias de Oliveira; Moraes, Vivian Cardoso (Seven Editora, 2024)
Studies with an environmental context are of great importance, such as the analysis of the Administrative Headquarters of the Forestry Foundation with the intention of the architects to contribute to the sustainability and regeneration of the surrounding areas, especially with the use of wood and the incorporation of CO₂. This is carried out during the growth of trees as it is a renewable material. The objective of the work is to study the design and construction process of this work. As a methodology is the case study and the form of analysis of the design process, construction, and structure through graphic analysis. DOI:https://doi.org/10.56238/sevened2024.026-042